Lowly who prevail : vistas to the work of Hjalmar Bergman - Bock, Sigge, 1943- (S. Bokke, 1990)
Deals with the work of Hjalmar Bergman from a theological point of view. Focuses on Bergman's "Komedier i Bergslagen," but also on the four novels "Markurells i Wadköping", "Herr von Hancken," "Farmor och Vår Herre," and "Flickan i frack."